Influência da substituição parcial do cimento Portland por Metacaulim nas propriedades mecânicas e na espessura de pasta do concreto permeável - Ferreira, Ayrton Rodrigues (Universidade do Vale do Rio dos Sinos, 2024)
The paved areas of cities mostly use impermeable coatings, which contribute to problems caused by floods and inundations. Permeable concrete coating is a way to mitigate these problems and promote the return to the natural hydrological cycle. Permeable concrete allows water to flow through its physical structure via interconnected macropores. Its physical structure is composed of coarse aggregate coated with cement paste. The paste must have an adequate consistency to avoid defects, failure in the aggregate coating, and clogging of the pores during concrete production. In this regard, the main objective of this research is to verify the influence of the partial replacement of cement by metakaolin on the mechanical and hydraulic properties, as well as the paste thickness of permeable concrete. Thus, the study proposed examining the amount of water to be added to the cement paste that provides the best consistency and allows satisfactory mixing with the aggregate. Four cement pastes were used: a reference paste and replacements of 5%, 10%, and 15% of the cement mass with metakaolin. Water content was tested until each mixture reached a spread of 100±5 mm, measured with the Kantro mini-cone. The uniform rheological behavior in all pastes studied was confirmed through squeeze-flow tests, showing that all pastes with metakaolin exhibited similar behavior when subjected to a force of up to 200 N with a mass displacement of approximately 5 mm. Four (04) permeable concrete mixtures were molded with the same metakaolin contents. Comparing the reference mixture with the replacements, it was observed that the 5% content achieved the best results at 28 days, with the axial compressive strength of 18.09 MPa increasing by about 7.36%, the tensile strength by diametrical compression of 2.73 MPa increasing by about 5.00%, the resistance to degradation by impact and abrasion of 56.18% increasing by about 4.74%, and the permeability coefficient of 0.00507 m/s increasing by about 58.93%. The 10% replacement content showed deterioration in most properties, and the 15% content proved unfeasible.
Keywords: Concreto permeável; Substituição parcial; Metacaulim; Espessura de pasta; Propriedades mecânicas e hidráulicas; Permeable concrete; Partial replacement; Metakaolin; Paste thickness; Mechanical and hydraulic properties; ACCNPQ::Engenharias::Engenharia Civil